Effect of Photodynamic Therapy Using Lasers on Periodontal Parameters in Patients with Chronic Periodontitis - Jassal, Jyotsna; Gupta, Shalini; Singh Tuli, Amrinder; Prakash Gupta, Prem; Mehrotra, Nidhi; Chauhan, Astha (Journal of Neonatal Surgery, 2025)
Background: Chronic periodontitis is a widespread inflammatory disease characterized by the destruction of supporting periodontal tissues, primarily driven by pathogenic microbial biofilms. While conventional scaling and root planing (SRP) is the cornerstone of treatment, its limitations in eradicating bacteria from complex anatomical sites necessitate adjunctive therapies. Antimicrobial photodynamic therapy (aPDT) offers a promising non-invasive approach, utilizing a photosensitizer activated by a specific light wavelength to generate reactive oxygen species, thereby targeting periodontopathogenicbacteria.This study aims to assess and compare the changes in probing pocket depth (PD) and clinical attachment level (CAL), following SRP alone versus SRP combined with antimicrobial photodynamic therapy using an 810 nm diode laser and Indocyanine Green (ICG) in patients with chronic periodontitis. Materials and Methods:A total of 42 systemically healthy patients diagnosed with moderate to severe chronic periodontitis (probing pocket depth ≥5mm) were recruited from the Outpatient Department of Periodontology, Seema Dental College and Hospital, Rishikesh, Uttarakhand. Participants were randomly assigned to two groups (n=21 each): Group A (Control Group) which received SRP alone, and Group B (Test Group) which received SRP followed by aPDT. For Group B, a 5mg/ml ICG solution was prepared and applied into the periodontal pockets, followed by irradiation with an 810 nm diode laser. Clinical parameters including Gingival Index, Plaque Index, Sulcus Bleeding Index, Probing Depth, and Periodontal Clinical Attachment Loss were assessed at baseline and 3 months post-treatment. All collected data was statistically evaluated. Results:The adjunctive use of laser-assisted aPDTlead to a statistically significant reduction in probing pocket depth and an improvement in clinical attachment level compared to SRP alone. This is based on previous research indicating that aPDT enhances the antimicrobial effects of SRP and contributes to the resolution of inflammation. Conclusion: This study provides evidence on the efficacy of laser-assisted photodynamic therapy as a valuable adjunct to conventional non-surgical periodontal treatment for chronic periodontitis, potentially leading to improved clinical outcomes and patient comfort.